Love is an adventure in evil: Sor Juana’s sonnets - Zavala, Iris M. (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
A discussion of Sor Juana’s love poems from a triple postructuralist perspective re-accented from Gilles Deleuze and M. Bakhtin: nomadism, a rizomatic writing of multiplicities and heterogeneities, and the grotesque, represented by a periferal Baroque verbal garb. Such a re-reading enables the narrative subject to be unstable and to constantly change the role and the voice, multiplying the narrative selves which come into textual existence through rarified ambiguities. The many faceted nature of the "female subject" in these erotic sonnets displays what is known as "beyond the pleasure principie", and they question what Lacan calls desire and the paradoxes of pleasure.